INDEPENDENSI PERAN JABATAN NOTARIS SEBAGAI PROFESI PENUNJANG PASAR MODAL - Lyanthi, Merline Eva (Jurnal Hukum Bisnis Bonum Commune, 2020)
AbstractThe capital market like other markets can be interpreted as a meeting place between the seller and the buyer to make transactions in the form of objects traded, including capital or funds. The existence of the capital market itself already exists in almost all countries in the world except for countries that are still unable to break away from unstable economic and political problems. The capital market has a strategic role to advance national development in order as a source of financing for the business world and investment for the community. In an effort to develop the capital market to be able to develop properly in Indonesia, the 1995 Capital Market Law No. 8 of 1995 was issued. The Capital Market Law aims to provide guarantees in the form of legal certainty for the parties involved in activities in Indonesia. Capital Market and to provide protection for the interests of the investor community to avoid practices that can harm either party. Capital market activities require the help of a number of professions that can support capital market activities, one of which is the Notary profession. Notary as a capital market supporting profession is regulated by the Capital Market Law. The role of the Notary Position in carrying out a capital market activity is required when carrying out the process of public offering of shares in terms of making and examining the validity of the deeds or agreements made by the Notary Public relating to the General Meeting of Shareholders and amendments to the Articles of Association or bylaws of parties or actors in the capital market and require the Notary to submit information in the form of input or provide an independent information suggestion.Keywords: capital market; notaryAbstrakPasar modal seperti pasar lainnya ialah dapat diartikan sebagai suatu tempat bertemunya antara penjual dengan pembeli untuk melakukan transaksi berupa objek yang diperjualbelikan antara lain modal atau dana. Keberadaan pasar modal itu sendiri sudah ada hampir diseluruh negara di dunia kecuali bagi negara-negara yang masih belum mampu untuk melepaskan diri dari permasalahan ekonomi dan politik yang belum stabil. Pasar modal memiliki suatu peranan yang strategis untuk memajukan pembangunan nasional dalam rangka sebagai sumber pembiayaan untuk dunia usaha dan investasi untuk masyarakat. Dalam rangka upaya mengembangkan pasar modal untuk dapat berkembangan dengan baik di Indonesia, maka Tahun 1995 diterbitkan Undang-Undang tentang Pasar Modal Nomor 8 Tahun 1995. Undang-Undang Pasar Modal ini bertujuan untuk memberikan jaminan berupa kepastian hukum bagi para pihak yang terlibat dalam kegiatan di Pasar Modal dan untuk memberikan perlindungan bagi kepentingan masyarakat pemodal agar terhindar dari praktik yang dapat merugikan salah satu pihak. Kegiatan pasar modal membutuhkan bantuan beberapa profesi yang dapat menunjang aktivitas pasar modal salah satunya ialah profesi Notaris. Notaris sebagai profesi penunjang pasar modal diatur oleh Undang-Undang Pasar Modal. Peran Jabatan Notaris dalam menjalankan suatu kegiatan pasar modal diperlukan pada saat melakukan proses penawaran umum saham dalam hal membuat dan meneliti keabsahan akta-akta atau perjanjian-penjanjian yang dibuat oleh Notaris yang berhubungan dengan Rapat Umum Pemegang Saham dan perubahan anggaran dasar atau anggaran rumah tangga pihak atau pelaku dalam pasar modal serta mewajibkan Notaris untuk menyampaikan informasi berupa masukan atau memberikan suatu saran informasi yang independen.Kata kunci: notaris; pasar modal